Fractionation and characterization of saccharides and lignin components in wood prehydrolysis liquor from dissolving pulp production. (1st August 2015) - Wang, Zhaojiang; Wang, Xiaojun; Jiang, Jungang; Fu, Yingjuan; Qin, Menghua
Highlights: Fractionation and characterization of saccharides and lignin components in wood pre-hydrolysis liquor was performed. High-value oligsaccharides consituted 87.2% of total saccharides (18.89 g/L) with xylooligosaccharide as the dominant component. Abundant phenolic hydroxyl groups make lignin components valuable in polymer industry. Incapability of member filtration in improving homogeneity of saccharides or lignin components was revealed. Abstract: Saccharides and lignin components in prehydrolysis liquor (PHL) from kraft-based dissolving pulp production was characterized after being fractionated using membrane filtration. The results showed that the membrane filtration provided a method for organics fractionation with considerable recovery rate, but exhibited some disadvantages. Besides the limited ability in purifying oligosaccharides (OS) due to the overlaps of molecular weight distribution with lignin components, the membrane filtration could not improve the homogeneity of OS as indicated by the analysis of chemical compositions and the degree of polymerization (DP), which may be ascribed to the linear conformation of OS. The characterization of lignin components indicated a great potential for polymer industry because of the remarkable content of phenolic hydroxyl groups (PhOH), especially for low molecular weight (LMW) fraction. It was concluded the organics in PHL provided streams of value-added chemicals. However, the practical significance thereof can be realized and maximized only when they are successfully and completely fractionated.